Antibody-Mediated Rejection in a Blood Group A-Transgenic Mouse Model of ABO-Incompatible Heart Transplantation. Issue 6 (June 2016) - Motyka, Bruce; Fisicaro, Nella; Wang, Szu-I; Kratochvil, Annetta; Labonte, Katrina; Tao, Kesheng; Pearcey, Jean; Marshall, Thuraya; Mengel, Michael; Sis, Banu; Fan, Xiaohu; d'Apice, Anthony J. F.; et al.
Abstract : Background: ABO-incompatible (ABOi) organ transplantation is performed owing to unremitting donor shortages. Defining mechanisms of antibody-mediated rejection, accommodation, and tolerance of ABOi grafts is limited by lack of a suitable animal model. We report generation and characterization of a murine model to enable study of immunobiology in the setting of ABOi transplantation. Methods: Transgenesis of a construct containing human A1- and H-transferases under control of the ICAM-2 promoter was performed in C57BL/6 (B6) mice. A-transgenic (A-Tg) mice were assessed for A-antigen expression by histology and flow cytometry. B6 wild-type (WT) mice were sensitized with blood group A-human erythrocytes; others received passive anti-A monoclonal antibody and complement after heart transplant. Serum anti-A antibodies were assessed by hemagglutination. "A-into-O" transplantation (major histocompatibility complex syngeneic) was modeled by transplanting hearts from A-Tg mice into sensitized or nonsensitized WT mice. Antibody-mediated rejection was assessed by morphology/immunohistochemistry. Results: A-Tg mice expressed A-antigen on vascular endothelium and other cells including erythrocytes. Antibody-mediated rejection was evident in 15/17 A-Tg grafts in sensitized WT recipients (median titer, 1:512), with 2 showing hyperacute rejection and rapid cessation of graft pulsation. Hyperacute rejection was observed in 8/8 A-Tg grafts after passive transfer of anti-A antibody and complement into nonsensitized recipients. Antibody-mediated rejection was not observed in A-Tg grafts transplanted into nonsensitized mice. Conclusions: A-Tg heart grafts transplanted into WT mice with abundant anti-A antibody manifests characteristic features of antibody-mediated rejection. These findings demonstrate an effective murine model to facilitate study of immunologic features of ABOi transplantation and to improve potential diagnostic and therapeutic strategies. Abstract : Motyka et al describe a novel transgenic mouse that expresses the human A1- and H-transferases under the ICAM-1 promoter, and show that such mice can serve as organ donors for investigations into anti-blood group A antibody-mediated rejection. Supplemental digital content is available in the text.